2012
DOI: 10.3389/fnhum.2012.00086
|View full text |Cite
|
Sign up to set email alerts
|

Specifying social cognitive processes with a social dual-task paradigm

Abstract: Automatic imitation tasks measuring motor priming effects showed that we directly map observed actions of other agents onto our own motor repertoire (direct matching). A recent joint action study using a social dual-task paradigm provided evidence for task monitoring. In the present study, we aimed to test (a) if automatic imitation is disturbed during joint action and (b) if task monitoring is content or time dependent. We used a social dual-task that was made of an automatic imitation task (Person 1: Task 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Most previous neuroimaging studies were not designed to reveal behavioral effects for different action-word types, which requires some sort of context or task manipulation, and their results cannot be compared to ours. Several behavioral studies have reported an interference between semantic sensorimotor features of linguistic stimuli and response execution (e.g., Boulenger et al., 2006 , Glenberg and Kaschak, 2002 , Liepelt et al., 2012 , Meteyard et al., 2008 ). The strongest evidence for a causal role of sensorimotor systems in semantic processing would be a specific break-down or facilitation of semantic processing after specific impairment or stimulation of sensorimotor systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous neuroimaging studies were not designed to reveal behavioral effects for different action-word types, which requires some sort of context or task manipulation, and their results cannot be compared to ours. Several behavioral studies have reported an interference between semantic sensorimotor features of linguistic stimuli and response execution (e.g., Boulenger et al., 2006 , Glenberg and Kaschak, 2002 , Liepelt et al., 2012 , Meteyard et al., 2008 ). The strongest evidence for a causal role of sensorimotor systems in semantic processing would be a specific break-down or facilitation of semantic processing after specific impairment or stimulation of sensorimotor systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rather than showing that word processing activates motor areas, we can potentially reveal whether the activation state of the motor system affects language processing. Similar paradigms have already been used in behavioral and event-related potential (ERP) research ( Boulenger et al., 2006 , Dalla Volta et al., 2009 , Glenberg et al., 2010 , Helbig et al., 2010 , Liepelt et al., 2012 , Sato et al., 2008 , Shebani and Pulvermüller, 2013 , Van Elk et al., 2008 , Van Elk et al., 2010 ). In our approach, we can study the effect of motor priming on both behavior and spatio-temporal brain dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also observed an SSE in blindfolded-sighted and seeing individuals who only differed in the amount of visual feedback during task performance. Indeed, it has been shown that vision substantially contributes to the coordination of shared actions and the understanding of others' intentions [47][49]. For example, there is evidence that the observation of others' gaze direction facilitates nonverbal communication in cooperative interaction [50] and changes the control of motor acts on the behavioral level [51][52], as well as on the cortical level [53][55].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors conclude from their results that people do co-represent them (e.g., Baus et al, 2014; Demiral et al, 2016; Dudarev & Hassin, 2016; Kuhlen & Abdel Rahman, 2017; Sebanz et al, 2003), while others conclude that they do not (e.g., Dolk et al, 2014; Liepelt et al, 2012; Saunders et al, 2017; Wenke et al, 2011; Yamaguchi et al, 2017b). Most alternative accounts of the mechanisms underlying seemingly social phenomena are “task-content-free.” For instance, they suggest that people use the partner as a spatial reference (Dolk et al, 2014) or that they represent who is going to respond (Wenke et al, 2011) and when the partner is going to respond (Liepelt et al, 2012). Thus, they do not speak to the possibility that an absence of action co-representation can still mean that people represent something about the content of what the partner is doing.…”
Section: Introductionmentioning
confidence: 95%
“…In the joint action literature, there is an ongoing debate whether and how people co-represent a partner’s task (e.g., Böckler et al, 2012; Dolk et al, 2014; Gambi et al, 2015; Liepelt et al, 2012; Sebanz et al, 2003; Wenke et al, 2011). Most studies have used paradigms, such as the Joint Simon task, in which two people share one task and each partner performs half of it.…”
Section: Introductionmentioning
confidence: 99%